Plasma levels of vascular endothelial growth factor during and after radiotherapy in combination with celecoxib in patients with advanced head and neck cancer - Halamka, Magdalena; Cvek, Jakub; Kubes, Jiri; Zavadova, Eva; Kominek, Pavel; Horacek, Jaroslav; Dusek, Ladislav; Feltl, David (Oral oncology, 2011)
Celebrex and radiotherapy in advanced head and neck cancer. This phase I dose-escalation study seeks to determine the phase II recommended dose of cyclooxygenase type 2 (COX-2) inhibitor in patients with locally advanced squamous cell head and neck (H&N) cancer, treated with accelerated radiotherapy. Anti-vasculogenic effect of this treatment on serum vascular endothelial growth factor (VEGF) is examined. Patients were irradiated with curative intent (72Gy in 6weeks). Celecoxib was administered throughout the radiotherapy course. Serum VEGF level were tested during radiotherapy and in follow-up. Tumor specimens were stained to quantify the COX-2 expression. Thirty-two patients completed the treatment. The dose of celecoxib was escalated (200, 400 and 800mg bid, then de-escalated to 600mg bid). The acute toxicity related to the treatment in the first and second cohort did not reach grade III; in the third cohort three patients had grade III radiation toxicity and one had celecoxib-related toxicity. In the last fourth cohort the toxicity was acceptable. Significant VEGF level drop (p=0.011) was found between radiation day 1 and post-treatment visit. Significant decrease (p=0.022) of the VEGF level was shown in patients with high COX-2 expression in the tumor. Phase II recommended dose of celecoxib combined with accelerated radiotherapy in advanced H&N cancer was 600mg bid. A significant decrease of the post-treatment serum VEGF level compared to the initial level was noticed only in patients with high COX-2 expression in tumors.
Keywords: dospělí; sulfonamidy; cyklooxygenasa 2; Humans; lidé středního věku; nádory hlavy a krku; Middle Aged; inhibitory cyklooxygenasy 2; Combined Modality Therapy; Carcinoma, Squamous Cell; Cyclooxygenase 2; Vascular Endothelial Growth Factor A; Cyclooxygenase 2 Inhibitors; mužské pohlaví; spinocelulární karcinom; vaskulární endoteliální růstový faktor A; Adult; Clinical Trials, Phase II as Topic; celekoxib; kombinovaná terapie; ženské pohlaví; lidé; Head and Neck Neoplasms; Pyrazoles; Aged; Celecoxib; senioři; Male; pyrazoly; Sulfonamides; klinické zkoušky, fáze II jako téma; Female